Archie Green : the making of a working-class hero - Burns, Sean (University of Illinois Press, 2011)
"Archie Green: The Making of a Working-Class Hero celebrates one of the most revered folklorists and labor historians of the twentieth century. Devoted to understanding the diverse cultural customs of working people, Archie Green (1917-2009) tirelessly documented these traditions and educated the public about the place of workers' culture and music in American life. Doggedly lobbying Congress for support of the American Folklife Preservation Act of 1976, Green helped establish the American Folklife Center at the Library of Congress, a significant collection of images, recordings, and written accounts that preserve the myriad cultural productions of Americans. Capturing the many dimensions of Green's remarkably influential life and work, Sean Burns draws on extensive interviews with Green and his many collaborators to examine the intersections of radicalism, folklore, labor history, and worker culture with Green's work. Burns closely analyzes Green's political genealogy and activist trajectory while illustrating how he worked to open up an independent political space on the American Left that was defined by an unwavering commitment to cultural pluralism"--